2017
DOI: 10.1007/s10646-017-1777-4
|View full text |Cite
|
Sign up to set email alerts
|

Gill damage and neurotoxicity of ammonia nitrogen on the clam Ruditapes philippinarum

Abstract: Ammonia nitrogen has been a potential menace to aquatic animals along the coastline of China. Presently, the toxicological effects of ammonia nitrogen were mainly concentrated on fishes, while little attention has been paid to molluscs. In this study, the clam Ruditapes philippinarum was used as the target animal to investigate the toxic effects of ammonia nitrogen. Our results showed that ammonia exposure could significantly reduce the integrity of lysosomes in a dose-dependent manner. Metabolite analysis rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 43 publications
3
20
0
Order By: Relevance
“…It has been suggested as a potential mediator for phospholipidosis during lysosome dysfunction (Balsinde et al, 2002). The significant variation of phospholipase A2 isozymes (PA3A/PA3B/PA5) gene after ammonia nitrogen exposure would attribute to the reduced integrity of lysosome membrane which we found in the previous study (Cong et al, 2017).…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…It has been suggested as a potential mediator for phospholipidosis during lysosome dysfunction (Balsinde et al, 2002). The significant variation of phospholipase A2 isozymes (PA3A/PA3B/PA5) gene after ammonia nitrogen exposure would attribute to the reduced integrity of lysosome membrane which we found in the previous study (Cong et al, 2017).…”
Section: Discussionsupporting
confidence: 54%
“…Our previous study revealed that ammonia exposure could significantly reduce the integrity of lysosome membrane, decrease the contents of glutamate and branched chain amino acid, decrease ATP supply, increase apoptosis ratios, decrease contents of neurotransmitters, reduce basal layer inside the filaments with the emergence of xenobiotic substances (Cong et al, 2017). It suggested that ammonia nitrogen exposure brought detrimental toxicity to R. philippinarum.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…When fish are exposed to excessively high alkalinity water, a large amount of mucus is secreted on the surface of the fish, and gills bleeding at the same time, causing serious death [37]. The adaptation process of fish to the high saline‐alkali water environment mainly refers to the process of changes in blood osmotic pressure and tissue enzyme activity of the fish body under short‐term saline‐alkali stress, as well as the process of self‐regulation and restoration to the initial state of fish body, which are regulated by the gene expression associated with enzyme activity through tissues such as the kidneys and gills [38]. Gills are the main organs of fish breathing, and their structural integrity directly affects the normal operation of gas exchange, filter food, osmotic pressure regulation, and waste excretion functions [39].…”
Section: Discussionmentioning
confidence: 99%